Modification of the existing maximum residue levels for fluazinam in onions, shallots and garlic. (26th July 2017) - ; Brancato, Alba; Brocca, Daniela; De Lentdecker , Chloé; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; Medina, Paula; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Adama Makhteshim submitted a request to the competent national authority in the Netherlands to set maximum residue levels (MRL) for the active substance fluazinam in onions, shallots and garlic. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all crops under consideration. An adequate analytical method for enforcement is available to control the residues of fluazinam in plant matrices. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of fluazinam according to the intended agricultural practices is unlikely to present a risk to consumer health.